GeoServer: il server geospaziale Open Source novità della nuova versione 2.3.0 - Giannecchini, Simone; Aime, Andrea (GEOmedia, 2013)
GeoServer è un server geospaziale Open Source sviluppato con tecnologia Java Enterprise per la gestione e l'editing di dati geospaziali secondo gli standard OGC e ISO Technical Committee 211. Esso fornisce le funzionalità di base per creare infrastrutture spaziali di dati (SDI) ed è progettato per essere interoperabile potendo pubblicare dati provenienti da ogni tipo di fonte spaziale utilizzando standard aperti. Open Source GeoSpatial server developed with Java Enterprise technology for managing, sharing and editing geospatial data according to the OGC and ISO TC 211 standards. GeoServer provides the basic functionalities to create spatial data infrastructures (SDI). GeoServer is designed for interoperability, it publishes data from any major spatial data source using open standards: it is the reference implementation of the Open Geospatial Consortium (OGC) Web Feature Service (WFS) and Web Coverage Service (WCS) standards, as well as a high performance certified compliant Web Map Service (WMS). GeoServer forms a core component of the Geospatial Web.